INFORMASI, INTERAKTIFITAS, DAN RELEVANSI INSTAGRAM REELS ADS DAN DAMPAKNYA TERHADAP ADVERTISEMENT PERFORMANCE EXPECTANCY - Ramadhan, Muhammad Daffa; Kurnia, Kurnia (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
The primary goal of this research was to explore the impact of information, interactivity, and relevance in Instagram Reels Ads, specifically focusing on their influence on ad performance expectations within the context of FitaminCylingCulture. The study takes a quantitative approach within the positivism paradigm. The target population consists of active users of social media who are followers of the Instagram account @FitaminCylingCulture. A total of 100 respondents were selected for the study based on the Lemeshow formula with a 10% margin of error. The sampling method employed was purposive, involving the selection of active followers of FitaminCyclingCulture who are also customers. Data analysis was conducted using partial least squares (PLS), which included testing the measurement model for validity and reliability, as well as assessing the statistical significance of the hypothesized relationships through structural model testing. The majority of respondents were located in the Jabodetabek region (94.2%), with the largest age group being 20-24 years old (63.5%). It was found that these three factors had a significant positive impact on advertisement performance expectations.